Active tectonic and volcanic mountain building as agents of rapid environmental changes and increased orchid diversity and long-distance orchid dispersal in the tropical Americas: opportunities and challenges - Kirby, Stephen H. (Lankesteriana: International Journal on Orchidology, 2016)
Tropical Latin America is a nexus of tectonic plates whose relative motions have led to rapid tectonic and volcanic mountain building in late Neogene time. Tropical mountain building, in turn, leads to highland “cloud forest” microclimates with increased rainfall, lower diurnal temperatures, and diverse microclimates. I have previously emphasized how the geologically recent growth of mountains has been localized in Central America and that this is likely a factor in the high diversity and endemism in those highlands. This paper will show that Andean uplift accelerated at 15 Ma ago and 5 Ma BP and continues to this day. This process evolved geographically among the cordilleras of the region. Givnish and others recently presented phylogenomic evidence that the diversity of many epiphytic orchids, including tribes found in the neotropics, also accelerated during this time interval.. Phylogenetic investigations of tropical orchid pollinators have shown that acceleration in speciation in such pollinators as hummingbirds, orchid bees, and flies occurred over this same time frame, suggesting that geologically driven environmental changes may have acted in concert with changes in orchid biology to speed up orchid diversity in these highlands. I also review some of the long-distance dispersal processes of orchids in the tropical Americas. River systems draining the Colombian Andes discharge into the Caribbean Sea and current-driven log-raft drifts and air suspension during cyclonic storms transport plants and animals from east to the west. Lastly I emphasize the need for the more information on orchid floras and species distribution in this hotspot.